2013
DOI: 10.1007/s00590-013-1348-1
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-associated complications following lower limb arthroplasty: a comparison of two prophylactic regimes

Abstract: Gentamicin with flucloxacillin is comparable with cefuroxime in rates of SSI and RTT but is associated with a significant increase in AKI. AKI is associated with additional morbidity and mortality. This association should be considered when choosing a suitable prophylactic regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…Antimicrobial stewardship guidance led many departments to move away from cephalosporins because of the increased risk of Clostridium difficile infection. However, it has been shown that some alternative regimens such as flucloxacillin and gentamicin are associated with increased incidence of AKI 18,[23][24][25] as a result of interstitial nephritis. In our study, there was no increased incidence of AKI with gentamicin/teicoplanin compared with cefuroxime.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial stewardship guidance led many departments to move away from cephalosporins because of the increased risk of Clostridium difficile infection. However, it has been shown that some alternative regimens such as flucloxacillin and gentamicin are associated with increased incidence of AKI 18,[23][24][25] as a result of interstitial nephritis. In our study, there was no increased incidence of AKI with gentamicin/teicoplanin compared with cefuroxime.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of studies showing that antibiotic prophylaxis consisting of gentamicin and flucloxacillin is associated with a higher rate of AKI than prophylaxis with cephlosporins (Craxford et al. 2014, Bailey et al. 2014, Bell et al.…”
Section: Discussionmentioning
confidence: 99%
“…2012, Craxford et al. 2014). We are aware that our study did not take account of information about other medications, perioperative bleeding, peri- and postoperative fluid administration, or comorbidity—including previous kidney disease.…”
Section: Discussionmentioning
confidence: 99%
“…also excluded patients with abnormal baseline renal function although the cutoff GFR was not mentioned (16). Five studies did not mention the use or requirement of renal replacement therapy.…”
Section: Figurementioning
confidence: 99%
“…Gentamicin and penicillin-antibiotic therapy as a surgical prophylaxis carries more risk for the development of AKI for patients undergoing orthopedic surgery as compared to cefuroxime therapy. In a subtype of orthopedic surgery, Craxford et al showed that total knee replacement (TKR) had a significantly higher rate of kidney injury than total hip replacement (THR) (16). They suggested that using pneumatic tourniquet in TKR produced ischemic metabolites and further increased risk of AKI when combined with gentamicin use.…”
Section: Figurementioning
confidence: 99%